Study of Changes in the Duration of the Siberian High Pressure Over Babylon Station During the Climatic Cycle (2010-2021) - Mahdi Jawad Al-Dujaili, Prof. Dr. Ali; Khamis Kahiyoush, Assist. Lect . Nada (Basra studies journal, 2025)
This research examines changes in the duration of the Siberian high-pressure system over Babel Station during the climatic cycle from 2010 to 2021. The study analyzes the total and monthly averages of the days the high-pressure system persisted, as well as the variations in its duration. The research also explores the period during which the pressure system dominates the Babylon Governorate, with its influence varying based on the system’s strength and competition with other atmospheric systems. Observations are taken at 00Z and 12Z for Babel Station, focusing on the changes in pressure at the 1000 millibar level. These changes, whether positive (indicating a rise) or negative (indicating a decrease), have a significant impact on Iraq’s weather and climate. The Siberian high-pressure system generally lowers temperatures, clears the air, and reduces upward air currents due to weakened air movement and a lack of green areas resulting from low rainfall. The study notes an increase in the number of days the Siberian high-pressure system persists, while the duration of secondary high-pressure centers has decreased during the 2010-2021 climatic cycle.